Analysis of deposit savings in Islamic and conventional banks - Putri Jamilah; Jaka Sriyana (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Indonesia is a country that implements a dual banking system. The progress of the conventional financial industry coincides with the development of the Islamic financial sector. This study discusses the influence of external factors namely inflation, broad money (M2), BI rate and internal factors namely return on asset (ROA) and operational efficiency ratio (OER) on profit-sharing of Islamic banking deposits and conventional banking deposits interest. The method used in this study was the Error Correction Model (ECM). Based on the results of the study, it can be concluded that inflation and broad money (M2) affects the profit-sharing of deposits. Whereas the conventional bank deposit interest is influenced by ROA, OER, BI rate, inflation, and M2. The fluctuation of external and internal variables has an impact on Islamic banks and conventional banks in determining interest and profit-sharing of deposits.